GAMBARAN TINGKAT KECEMASAN PADA WARGA YANG TINGGAL DI DAERAH RAWAN BANJIR KHUSUSNYA WARGA DI KELURAHAN TIKALA ARES KOTA MANADO - Lamba, Chaflin T.; Munayang, Herdy; Kandou, Lisbeth F. J. (Universitas Sam Ratulangi, 2017)
Abstract: Anxiety disorders, classified as psychiatric disorders, are usually resulting from a complex interaction of biological, psychological, and psychosocial elements. Anxiety warns the threat of injury to the body, fear, despair, the possibility of punishment, or the frustration of the need for enhanced social body, separation from loved ones, interference with the success or status of a person, and ultimately a threat to the unity or wholeness of a person. People living in areas prone to floods are assumed to suffer from anxiety of the coming floods. This study was aimed to assess the anxiety among people living in flood-prone areas by using sociodemofraphic data and questionnaire of Hamillton Anxiety Rating Scale (HARS). This was a descriptive qualitative study with a cross sectional design. There were 30 respondents that met the inclusion and exclusion criteria. The results showed that 2 (6.7%) respondents did not have any anxiety disorder; 10 (33.3%) people had mild anxiety disorders; 12 (40%) people had moderate anxiety disorders; and 6 (20.0%) people had severe anxiety disorders. Conclusion: The majority of people living in flood-prone areas suffered from anxiety and the most common type of anxiety was mild anxiety.Keywords: anxiety, flood prone areas, HARSAbstrak: Gangguan kecemasan digolongkan sebagai gangguan kejiwaan, umumnya diakibatkan oleh interaksi kompleks dari elemen biologis, psikologis, dan psikososial. Kecemasan memperingatkan ancaman cedera pada tubuh, rasa takut, keputusasaan, kemungkinan hukuman, atau frustrasi dari kebutuhan sosial tubuh, perpisahan dari orang yang dicintai, gangguan pada keberhasilan atau status seseorang, dan akhirnya ancaman pada kesatuan atau keutuhan seseorang. Sebagian masyarakat yang tinggal di daerah rawan banjir mengalami kecemasan akibat takut terkena dampak bencana banjir. Penelitian ini bertujuan untuk menilai gangguan kecemasan pada warga yang berada di daerah rawan banjir dengan menggunakan data sosiodemografik dan kuesioner Hamillton Anxiety Rating Scale (HARS). Jenis penelitian ialah deskriptif-kualitatif dengan desain potong lintang. Terdapat 30 responden yang memenuhi kriteria inklusi dan eksklusi. Hasil penelitian memperlihatkan responden yang tidak mengalami gangguan kecemasan sebanyak 2 orang (6,7%); gangguan kecemasan ringan sebanyak 10 orang (33,3%); gangguan kecemasan sedang sebanyak 12 orang (40%); dan gangguan kecemasan berat sebanyak 6 orang (20,0%). Simpulan: Sebagian besar masyarakat yang tinggal di daerah rawan banjir mengalami kecemasan dan terbanyak ialah kecemasan sedang.Kata kunci: kecemasan, daerah rawan banjir, HARS